The Effect of Financial Literacy, Financial Technology, and Digital Marketing Effect on Business Suistainibility in MSMEs in Magelang City - Niagasi, Ariq Fikria; Kurnia, Marlina; Safitri, Wahyu (Universitas Muhammadiyah Magelang, 2025)
This article examines